2022
DOI: 10.3389/fmed.2022.904756
|View full text |Cite
|
Sign up to set email alerts
|

Activation of angiotensin-converting enzyme 2 ameliorates metabolic syndrome-induced renal damage in rats by renal TLR4 and nuclear transcription factor κB downregulation

Abstract: BackgroundMetabolic syndrome (MetS) is an independent risk factor for chronic kidney disease (CKD) through many mechanisms, including activation of the renin–angiotensin system. The deleterious effects of angiotensin II (Ang II) can be counterbalanced by angiotensin-converting enzyme 2 (ACE2). Diminazene aceturate (DIZE), an anti-trypanosomal drug, can activate ACE2.ObjectiveThis study aimed to investigate the possible reno-protective effects of DIZE in MetS rats with elucidation of related mechanisms.Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Basic biometric parameters, as well as concentrations of angiotensin peptides, were measured in order to determine the condition of all experimental animals with emphasis on the main effects of systemic ACE2 inhibition and TAX treatment. The increase in BW gain following the ACE2 inhibition observed in this experiment is consistent with data showing a BW decrease after the administration of an ACE2 activator [22] as well as the documented negative correlation between circulating ACE2 levels and BW in rats [23]. We observed a decrease in BW gain following the TAX treatment mainly in ACE2-inhibited SHRs to values comparable to TAX-treated control SHRs.…”
Section: Basic Biometric Parameters and Angiotensin Peptides Concentr...supporting
confidence: 92%
“…Basic biometric parameters, as well as concentrations of angiotensin peptides, were measured in order to determine the condition of all experimental animals with emphasis on the main effects of systemic ACE2 inhibition and TAX treatment. The increase in BW gain following the ACE2 inhibition observed in this experiment is consistent with data showing a BW decrease after the administration of an ACE2 activator [22] as well as the documented negative correlation between circulating ACE2 levels and BW in rats [23]. We observed a decrease in BW gain following the TAX treatment mainly in ACE2-inhibited SHRs to values comparable to TAX-treated control SHRs.…”
Section: Basic Biometric Parameters and Angiotensin Peptides Concentr...supporting
confidence: 92%
“…In rat models, studies have shown that vascular ACE2 overexpression protects the kidneys against aging-induced renal dysfunction, 28 and the activation of ACE2 has been reported to have a renoprotective effect. 29 Recently, a large-scale study on the association between plasma ACE2 and the risk of CVD has been published. 30 However, there are still few clinical reports on the association between ACE2 and the prognosis of CKD, especially DKD, and our current report provides an important perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Adipocyte hypertrophy is present in MS rats and is the major source of inflammatory cytokines and a peptide hormone, leptin; research reports that leptin can enhance RAS 14 , 15 . Hyperactivity of RAS contributes to metabolic disorder-related complications 16 , 17 . Moreover, an increase in RAS components including angiotensin-converting enzyme (ACE), angiotensin II (ang II), and angiotensin II receptor type 1 (AT 1 R) in local tissue and circulation were seen in diet-induced MS in rats 18 .…”
Section: Introductionmentioning
confidence: 99%